Cho a và b thỏa mãn đẳng thức a.(a+2b)³-b.(2a+b)³=0 Tính M=a²-b²

Cho a và b thỏa mãn đẳng thức a.(a+2b)³-b.(2a+b)³=0
Tính M=a²-b²

1 bình luận về “Cho a và b thỏa mãn đẳng thức a.(a+2b)³-b.(2a+b)³=0 Tính M=a²-b²”

  1. Giải đáp + Lời giải và giải thích chi tiết:
    Ta có :
    a(a+2b)^3-b(2a+b)^3=0
    <=> a(a^3+6a^b+12ab^2+8b^3)-b(8a^3+12a^2b+6ab^2+b^3) = 0
    <=> a^4+6a^3b+12a^2b^2+8ab^3-8a^3b-12a^2b^2-6ab^3-b^4=0
    <=> a^4-b^4-2a^3b+2ab^3=0
    <=> (a^2-b^2)(a^2+b^2)-2ab(a^2-b^2)=0
    <=> (a^2-b^2)(a-b)^2=0
    <=> (a-b)(a+b)(a-b)^2=0
    <=>[a+b=0ab=0
     <=> a=+-b
    TH1 :  a = b =>M = a^2-b^2 = a^2 – a^2 = 0
    TH2 : a=-b=>M = a^2-b^2 = (-b)^2 – b^2 =0
    Vậy M = 0
    #nth

    Trả lời

Viết một bình luận

Câu hỏi mới